PENGEMBANGAN AGRIBISNIS USAHATANI JAGUNG DI KABUPATEN KOTAWARINGIN BARAT - Novi Nurhayati (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2018)
Corn is a food crop commodity that can be used as a substitute for rice, but it can also be used as animal feed. The purpose of this study is the prospect and strategy of agribusiness development of corn farming in Kotawaringin Barat Regency. The type of data required in this study is secondary data and primary data. The number of samples in this study amounted to 100 respondents. The method used in this research is SWOT analysis. The result of this research is the development of corn farming agribusiness has prospect to be developed in Kotawaringin Barat regency because have power to seize the opportunity that exist. The strategies used in agribusiness development of maize farming are (1) to increase the existing institutions in farmer groups to utilize government support in the development of corn farming agribusiness; (2) improving the performance of farmer groups by utilizing the presence of extension agents, to meet demand for corn in the market; (3) improving the quality of human resources to achieve the high value added opportunities of maize.